Pemberian Jus Tomat terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Trimester III di Puskesmas Bonorowo Kebumen - Novyriana, Eka; Caesarani, Monika Rahayu (Prosiding University Research Colloquium, 2019)
Anemia during pregnancy may be caused by lack of food supply in the beginning of pregnancy or because of anemia that a mother suffer from before pregnancy. To overcome this, the government provide blood-boosting tablets. The combination of blood boosting tablets and vitamin C is good to help absorb iron. Most pregnant mothers do not like drug of vitamin C. The writer is interested in providing tomato juice instead of drugs to increase hemoglobin level of trimester III pregnant mothers. To know the result of midwifery care for anemic pregnant mothers by giving tomato juice to increase hemoglobin level of trimester III pregnant mothers. It is an analytical descriptive with a case study approach. The samples are trimester III pregnant mothers suffering from anemia. Data were collected through interview and observations, literary study and documentation. After being given tomato juice for 28 days, there was an increase in hemoglobin level, i.e. 10.1 g/dL to 13 g/dL (participant 1), 10.1 g/dL to 13.2 g/dL (participan 2), 9.3 g/dL to 12.4 gr/dL (participant 3), 10.1 g/dL to 11.4 g/dL (participant 4), 10.8 g/dL to 11.5 g/dL (participant 5). Tomato juice can increase hemoglobin level of participants.